2021
DOI: 10.7717/peerj.11282
|View full text |Cite
|
Sign up to set email alerts
|

A Toll-like receptor identified in Gigantidas platifrons and its potential role in the immune recognition of endosymbiotic methane oxidation bacteria

Abstract: Symbiosis with chemosynthetic bacteria is an important ecological strategy for the deep-sea megafaunas including mollusks, tubeworms and crustacean to obtain nutrients in hydrothermal vents and cold seeps. How the megafaunas recognize symbionts and establish the symbiosis has attracted much attention. Bathymodiolinae mussels are endemic species in both hydrothermal vents and cold seeps while the immune recognition mechanism underlying the symbiosis is not well understood due to the nonculturable symbionts. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Previous studies have reported high levels of PRRs in the symbiotic gill tissue of bathymodiolines, such as G. platifrons , B. septemdierum , and B. azoricus ( Bettencourt et al, 2014 ; Chen et al, 2021 ; Ikuta et al, 2019 ; Li et al, 2020 ; Wang et al, 2019 ), suggesting their importance in symbiosis. Both TLRs and PGRPs have been suggested to participate in endosymbiont establishment and symbiosis regulation ( Li et al, 2021 ; Sun et al, 2017 ). TLRs and PGRPs also function in pathogenic infection, with the latter able to induce phagocytosis ( Bunet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported high levels of PRRs in the symbiotic gill tissue of bathymodiolines, such as G. platifrons , B. septemdierum , and B. azoricus ( Bettencourt et al, 2014 ; Chen et al, 2021 ; Ikuta et al, 2019 ; Li et al, 2020 ; Wang et al, 2019 ), suggesting their importance in symbiosis. Both TLRs and PGRPs have been suggested to participate in endosymbiont establishment and symbiosis regulation ( Li et al, 2021 ; Sun et al, 2017 ). TLRs and PGRPs also function in pathogenic infection, with the latter able to induce phagocytosis ( Bunet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The internalized bacteria were then eliminated by antibacterial proteins such PRRs in the host play irreplaceable roles in the immune recognition of symbionts. To further decode the immune recognition of symbiosis, several PRR proteins that may interact with methanotrophic symbionts were studied to understand their molecular characteristics and expression patterns (Chen et al 2019;Li et al 2020Li et al , 2021. Six candidate PRRs, including leucine-rich-repeat-domain-containing protein, TLR13, TLR2, integrin, vacuolar sorting protein and matrix metalloproteinase 1, were selected by methane-oxidizing bacteria or lipopolysaccharide pull-down assays, suggesting their key role in symbiont recognition.…”
Section: The Molecular Basis For Establishing and Maintaining Symbiosismentioning
confidence: 99%